2003
DOI: 10.1002/ejoc.200300298
|View full text |Cite
|
Sign up to set email alerts
|

Proximate, “Parallel‐In‐Plane” Preoriented Bis(diazenes) − In‐Plane Delocalized Bis(homoconjugated) 4N/5(6)e Anions

Abstract: Synthetic details are presented for a series of more or less rigid, “parallel‐in‐plane” preoriented bis(diazenes), with N=N/N=N distances (d) of 3.3−2.9 Å and interorbital angles (ψ) of 142−164° (X‐ray crystal structures). DFT calculations (B3LYP/6−31G*) and one‐/two‐electron reduction experiments with the two least preoriented, most “distant” bis(diazenes) (dN=N/N=N ca. 3.3 Å; ψ 142−146°) provide more insight into the structural prerequisites for bis(homoconjugative) in‐plane electron delocalization in 4N/5e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…Bisdiazene 3 (Figure 2 a) is more flexible, and the transannular distances are significantly greater than in 1 ( d N⋅⋅⋅N =3.124 Å, ω =159.3°) 1b,d. Still, the bridgehead methyl groups provide kinetic stabilization, and (Li + ) 2 3 2− was found to be highly persistent 1b.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisdiazene 3 (Figure 2 a) is more flexible, and the transannular distances are significantly greater than in 1 ( d N⋅⋅⋅N =3.124 Å, ω =159.3°) 1b,d. Still, the bridgehead methyl groups provide kinetic stabilization, and (Li + ) 2 3 2− was found to be highly persistent 1b.…”
Section: Methodsmentioning
confidence: 99%
“…The single‐determinant calculations used here provide upper16 boundaries for the electron delocalization as determined by δ ( Ω i , Ω j ) and for the degree of covalent transannular NN bonding. Given the experimentally observed significant shortening of the transannular NN distances in the highly rigid cage of 1 upon reduction, hardly any doubts can remain that the compounds described here, which represent the series of 4 N/6 e dianions,1 contain molecules with four cyclically bonded nitrogen atoms1d in form of the bishomotetrazete dianion substructure (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…The planar cyclic tetranitrogen molecule is isoelectronic with the cyclobutadiene. The synthesis of some compounds with planar cyclic normalN42 ions are reported earlier . Geier et al in a combine experimental and theoretical study revealed the in‐plane bis‐homoaromaticity in tetranitrogen dianions.…”
Section: Introductionmentioning
confidence: 84%
“…Das Bisdiazen 3 (Abbildung 2 a) ist flexibler und signifikant weniger nahgeordnet als 1 ( d N⋅⋅⋅N =3.124 Å, ω =159.3°) 1b,d. Dennoch erwies sich (Li + ) 2 ‐ 3 2− , kinetisch stabilisiert durch die Brückenkopf‐Methylgruppen, als sehr persistent 1b.…”
Section: Methodsunclassified